INSTAGRAM @dishubkotabogor SEBAGAI MEDIA PEMENUHAN KEBUTUHAN INFORMASI LALU LINTAS - Utami, Arizka Dewi; Fitriah, Maria; Agustini, Agustini (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
The digital era has transformed how government institutions communicate with the public, with social media becoming an effective medium for information dissemination. Instagram, as a visual-based platform, plays an essential role in delivering traffic-related information interactively and in real time. This study aims to analyze the utilization of Instagram features by the Bogor City Transportation Department in fulfilling traffic information needs among followers of the @dishubkotabogor account and to examine the effect of feature utilization on information fulfillment. This research employed a quantitative descriptive approach using a survey method. The sample consisted of 394 respondents, all followers of the department’s official Instagram account, selected through simple random sampling. Data were analyzed using simple linear regression to determine the relationship between feature usage and the fulfillment of information needs. The results show that the use of Instagram features falls into the “good” category, with feed posts being the most effective feature in disseminating traffic conditions, weekend operational schedules of Uncal vehicles, and public transportation services such as BISKITA. The overall information fulfillment level was also categorized as good, with the Current Need Approach showing the highest level among other need approaches. These findings indicate a positive and significant influence between the utilization of Instagram features and the fulfillment of traffic information needs. Thus, social media plays a strategic role in enhancing public communication and transparency within government institutions, particularly in the Bogor City Transportation Department. ABSTRAKPerkembangan era digital telah mengubah cara instansi pemerintah berkomunikasi dengan masyarakat, salah satunya melalui media sosial. Instagram menjadi platform efektif untuk menyebarkan informasi secara cepat dan interaktif. Penelitian ini bertujuan untuk menganalisis tingkat pemanfaatan fitur Instagram oleh Dinas Perhubungan Kota Bogor dalam memenuhi kebutuhan informasi lalu lintas para pengikut akun @dishubkotabogor serta menguji pengaruh antara pemanfaatan fitur tersebut terhadap pemenuhan kebutuhan informasi. Penelitian menggunakan pendekatan kuantitatif deskriptif dengan metode survei. Sampel penelitian berjumlah 394 responden yang merupakan pengikut akun Instagram Dinas Perhubungan Kota Bogor. Pengambilan sampel dilakukan dengan teknik simple random sampling, sedangkan analisis data menggunakan regresi linier sederhana untuk mengukur hubungan antarvariabel. Hasil penelitian menunjukkan bahwa pemanfaatan fitur Instagram tergolong baik, dengan feed post menjadi fitur paling dominan dalam penyebaran informasi terkait kondisi lalu lintas, jadwal operasional kendaraan Uncal, dan layanan transportasi publik seperti BISKITA. Pemenuhan kebutuhan informasi juga berada pada kategori baik, dengan pendekatan Current Need Approach menunjukkan capaian tertinggi dibandingkan pendekatan lainnya. Temuan ini menegaskan adanya pengaruh positif dan signifikan antara pemanfaatan fitur Instagram dan pemenuhan kebutuhan informasi lalu lintas. Artinya, media sosial berperan strategis dalam meningkatkan efektivitas komunikasi publik dan transparansi informasi di lingkungan pemerintahan, khususnya pada Dinas Perhubungan Kota Bogor.